Friendly visiting and partial enquiry (proof copy)
1902-02 1902 1900s 15 pages 12 the splint it would be badly looked after, and reported the home poor and close. With the concurrence, therefore, of the surgeon, the child was sent to a Children's Hospital, where the splint was not needed, and on leaving there was sent to a Country Home to complete the cure. Of cases sent for partial inquiry the following are types :— No. 1.— A woman brought children of 12 and 14, describing her husband as a painter and decorator, while she herself had boarders. She declared herself quite unable to pay for their treatment, and permitted C.O.S. inquiry. This proved the man to be a house and estate agent, and, as the woman had made some other false statements, she was dismissed although full inquiry had not been made as to income, &c. No. 2.— A patient described her husband as a potman. Inquiry proved him to be a public-house manager in a good thoroughfare, with all his family earning. It does not appear to me there can be any large increase in the numbers sent for partial inquiry, for when told that, 'should they wish to continue their treatment at the hospital, I must verify their statements,' they usually reply to the effect that 'they will not trouble the hospital to do that,' or that 'there are plenty more hospitals they can go to where they are not so particular!' This is unsatisfactory, but at present I cannot quite see how it can be altered. It is, however, a great help to know one is able to verify patients' statements, and I trust District Committees will continue to stand by us in this respect, for without their assistance an Almoner's work would be as 'inefficient and superficial' as our keenest opposers hold it to be. January 6, 1901. III. — WESTMINSTER HOSPITAL. REPORTS BY MISS NUSSEY, Almoner APRIL 1 TO DECEMBER 31, INCLUSIVE. (Out-patient Department closed for five weeks in the summer for cleaning, &c.) Number of patients interviewed 3,388 „ „ „ recommended to join clubs, &c. 662 Judged able to pay a general practitioner. Sent away 24 Discharged themselves 109 Not as yet returned 10 143 378/IMSW/A/1/1/9